Optimasi Kondisi Fermentasi Whey Dangke sebagai Produk Minuman dengan Response Surface Methodology - Fatma Maruddin; Soeparno Soeparno; Nurliyani Nurliyani; Chusnul Hidayat; Muhammad Taufik (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
Dangke whey is a dangke by-product that has not been widely utilized. Dangke whey is separated from curd using thepapaya latex as source of enzymes. The objectives of the study were to optimize fermentation conditions (tapioca level,inoculum level, and incubation time) of whey from dangke waste by using a response surface methodology. Commerciallyfermentative beverage was used as a target to determine the optimal conditions. Whey was mixed with tapioca level of0, 0.35, 0.7, 1.05, and 1.4%, and was heated by stirring for 5 minutes at temperature of 70 oC. The whey was pasteurizedat the temperature of 80 oC for 30 minutes. The whey was cool, and inoculated with L.acidophilus at the level of 1,3, 5, and 7%, and incubated at 37 °C for 8, 12, 16, 18, and 24 hours, respectively. The characteristics of fermentationbeverage obtained by the addition of inoculum level of 5%, tapioca 0.7% level and incubated for 16 hours were similarto the characteristics of commercially fermentative beverage. The characteristics of fermentated beverage were asfollows: lactic acid was 0.58%, viscosity was 0.21 poise and pH was 3, 7, respectively. These characteristics could beobtained by optimization of fermentation conditions by using RSM method.ABSTRAKWhey dangke merupakan limbah dangke yang belum banyak dimanfaatkan. Whey dangke dipisahkan dari curdmenggunakan getah buah pepaya sebagai sumber enzim. Penelitian ini bertujuan untuk mengoptimasi kondisifermentasi (level inokulum, waktu inkubasi dan level tapioka) whey limbah dangke sebagai produk minuman denganresponse surface methodology. Minuman fermentasi komersial digunakan sebagai target dalam menentukan kondisioptimal. Whey dicampur tepung tapioka level 0, 0,35., 0,7., 1,05 dan 1,4% dan dipanaskan sambil diaduk selama 5menit suhu 70 oC. Whey selanjutnya dipasteurisasi suhu 80oC selama 30 menit. Setelah dingin diinokulasi L.acidophiluslevel 1, 3, 5, dan 7% serta diinkubasi suhu 37 oC selama 8, 12, 16, 18 dan 24 jam. Karakteristik produk minuman yangdiperoleh dengan penambahan level inokulum 5%, tapioka level 0,7% dan diinkubasi 16 jam hampir sama karakteristikminuman fermentasi komersial adalah kandungan asam laktat 0,58%, viskositas 0,21 poise dan pH 3,7. Karakteristiktersebut dapat didekati dengan mengoptimasi kondisi fermentasi menggunakan metode RSM.